Efektivitas Konsumsi Bahan Olahan Kedelai terhadap Usia Menopause - Rauf, Maruwaty (Journal Midwifery Jurusan Kebidanan Politeknik Kesehatan Gorontalo, 2020)
The increasing number of menopause in an area is triggered by the number of women experiencing early menopause. This can be minimized if women often consume foods that contain isoflavones that we can find in soybeans. This study aims to analyze the effectiveness of consumption of processed soy materials on menopause age in Gorontalo City Health Center. The type of research is Analytical Survey with a cross-sectional approach which was carried out from June 2016 to July 2016 The number of respondents was 50 people, who were interviewed using a food frequency questionnaire (FFQ). This study used a purposive sampling technique. The results of the study were based on the chi-square test analysis with a significance degree of = 0.05 with the result that there was an effectiveness of processed soybean ingredients with menopause age in Gorontalo City Health Center, with the acquisition of the Sig value. (2-sided) is 0.000 with a value of = 0.05 = (0.000 < 0.05%). The conclusion obtained is that the consumption of processed soybean ingredients is effective with menopause age in Gorontalo City Health Center.